2004
DOI: 10.1071/en04057
|View full text |Cite
|
Sign up to set email alerts
|

Organic Trace Gases in the Atmosphere: An Overview

Abstract: Environmental Context. The major carbon-containing atmospheric gases (carbon dioxide, carbon monoxide, and methane) are found in the atmosphere at the parts-per-million levels, where they affect physical phenomena such as the greenhouse effect. There are however many more carbon-containing gases at much lower levels with many and varied roles; in the main these gases are more chemically active and affect principally chemical phenomena such as the ozone budget. Abstract. An overview of atmospheric organic trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 228 publications
(220 reference statements)
1
52
0
Order By: Relevance
“…A major precursor of HCHO in such regions is isoprene whose emission comprises more than 40% of the total VOC surface flux on a global scale. Its global emissions are estimated to be about 500 Tg yr −1 , a number exceeding by far the estimates for the anthropogenic sources (Williams, 2004). In addition to the hydrocarbons oxidation, HCHO also has known primary sources from direct emissions of biomass burning Holzinger et al, 1999;Yokelson et al, 1999;Andreae and Merlet, 1999), industrial processes and fuel combustion (Anderson et al, 1994;Geiger et al, 2002) and vegetation (Seco et al, 2006 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…A major precursor of HCHO in such regions is isoprene whose emission comprises more than 40% of the total VOC surface flux on a global scale. Its global emissions are estimated to be about 500 Tg yr −1 , a number exceeding by far the estimates for the anthropogenic sources (Williams, 2004). In addition to the hydrocarbons oxidation, HCHO also has known primary sources from direct emissions of biomass burning Holzinger et al, 1999;Yokelson et al, 1999;Andreae and Merlet, 1999), industrial processes and fuel combustion (Anderson et al, 1994;Geiger et al, 2002) and vegetation (Seco et al, 2006 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…ref. [1] and references therein). Many terrestrial sources of such species have been characterised and quantified, [2][3][4] including anthropogenic emissions associated with the production and use of fossil fuels (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Recently, however, it has become apparent that the surface ocean can play an important role in the budgets of both organic trace gases and aerosols. For example, the surface ocean has been shown to be a massive reservoir for oxygenated organic species [1,6] and a recent study of marine aerosols at a coastal site in Ireland [7] showed that the organic fraction contributes significantly (63%) to the sub-micrometer particle mass of aerosols collected over the North Atlantic Ocean during phytoplankton bloom periods. These high-organic-fraction aerosols may be generated directly by bubble bursting at the organic-rich sea surface, or by the emission and subsequent oxidation of biogenic gases that produce semivolatile products and aerosol.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high reactivity of BVOC with the primary oxidizing agent OH and their propensity to form particles, these emissions can affect global oxidation chemistry and the Earth's radiation budget (Williams 2004 and references therein). One much studied sub-set of BVOC is the family of monoterpenes, which are emitted by terrestrial plants to the atmosphere in large amounts (ca.…”
Section: Introductionmentioning
confidence: 99%